2000
DOI: 10.1074/jbc.m007148200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Constitutively Active Mutants of Mammalian Adenylyl Cyclase

Abstract: A genetic screen in Saccharomyces cerevisiae identified mutations in mammalian adenylyl cyclase that activate the enzyme in the absence of G s ␣. Thirteen of these mutant proteins were characterized biochemically in an assay system that depends on a mixture of the two cytosolic domains (C 1 and C 2 ) of mammalian adenylyl cyclases. Three mutations, I1010M, K1014N, and P1015Q located in the ␤4-␤5 loop of the C 2 domain of type II adenylyl cyclase, increase enzymatic activity in the absence of activators. The K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Similarly, we found that the found to increase the affinity of the two domains for gsa-1 strong gain-of-function mutation could not bypass each other (Hatley et al 2000). We note that the acy-1 the larval arrest phenotype of acy-1 nulls, although the (md1756) mutation occurs at a known contact point gsa-1(ce81); acy-1(pk1279) double mutants, like acy-1 between the two domains, as revealed by structural stud-(pk1279) single mutants, can survive for days after hatchies of vertebrate adenylyl cyclases (Tesmer et al 1997;ing (Reynolds et al 2005).…”
Section: Downstream Of the Catalytic Glutamine This Residue Is 2005)mentioning
confidence: 68%
“…Similarly, we found that the found to increase the affinity of the two domains for gsa-1 strong gain-of-function mutation could not bypass each other (Hatley et al 2000). We note that the acy-1 the larval arrest phenotype of acy-1 nulls, although the (md1756) mutation occurs at a known contact point gsa-1(ce81); acy-1(pk1279) double mutants, like acy-1 between the two domains, as revealed by structural stud-(pk1279) single mutants, can survive for days after hatchies of vertebrate adenylyl cyclases (Tesmer et al 1997;ing (Reynolds et al 2005).…”
Section: Downstream Of the Catalytic Glutamine This Residue Is 2005)mentioning
confidence: 68%
“…Finally, the maximal stimulated activity is ϳ10-fold higher for the soluble enzyme (21,22). Moreover, the F400Y mutation in the type V molecule, which showed increased basal activity and sensitivity to G s ␣ and forskolin, did not alter the enzymatic activity of the soluble construct bearing the same substitution (24,25). It has been shown that the C1b domain of adenylyl cyclases (which is absent in these constructs) possesses regulatory properties (26 -31).…”
Section: Discussionmentioning
confidence: 99%
“…Hatley et al (25) isolated mutants of the type II enzyme that rescued the cyclase-null Saccharomyces cerevisiae strain. All mutations mapped to the cytoplasmic loops of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hatley et al (2000) created constitutively active mammalian adenylyl cyclase mutants through single amino acid substitutions, which increased the interaction of the two cytosolic domains of the adenylyl cyclase responsible for the catalytic activity (Tang and Gilman, 1995). One of those mutants, namely P1015Q has a similar amino acid change to our FAC1 P1441S gain-of-function allele, from a rigid proline to a non-polar glutamine (Hatley et al, 2000). Thus the change from proline to a non-polar serine in FAC1 P1441S could potentially cause similar structural changes, which increase the interaction between the substrate binding domain and the catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…In a constitutively active mutant of the Dictyostelium adenylyl cyclase, a mutation in the first cytoplasmic loop was thought to bring this domain closer to the second cytoplasmic loop, which might mimic activation by G proteins (Parent and Devreotes, 1996). Similarly, Hatley et al (2000) created constitutively active mammalian adenylyl cyclase mutants through single amino acid substitutions, which increased the interaction of the two cytosolic domains of the adenylyl cyclase responsible for the catalytic activity (Tang and Gilman, 1995). One of those mutants, namely P1015Q has a similar amino acid change to our FAC1 P1441S gain-of-function allele, from a rigid proline to a non-polar glutamine (Hatley et al, 2000).…”
Section: Discussionmentioning
confidence: 99%